METHODS OF DEVELOPING CHILDRENʼS PSYCHOLOGY AND SPEECH THROUGH ACTION GAMES OF PRESCHOOL EDUCATION (Scientific journal of the Fergana State University, 2024)
Paying attention to the mental state and fluency of speech during the development of children from a young age is the main link for these children to find their place in society and continue their activities so that there are no delays in their work later. In this regard, action games can be the main tool for educating children in an interesting way. In this article, the significance of mobile games for stabilizing the childʼs mentality and speech is considered, and a small research is conducted on them, and mobile games are evaluated according to the level of influence.